BURUH PEREMPUAN DI TENGAH KUBANGAN PARA KORUPTOR - Triana Sofiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
The Center of hegemony, which is built on the common values common interests between the rulers and capitalists who incidentally are in the sex of